Women and Restaurants in the Nineteenth-Century United States. (September 2014) - Freedman, Paul
Abstract: Restaurants flourished in the nineteenth–century United States as places for entertainment, social positioning, business advancement as well as dining. Women were admitted with restrictions that affected especially women alone or all-female groups. The article looks at the management of women's presence in the quasi-public space of the restaurant and how attitudes changed. It also examines the identification of women's supposed preferences for light, dainty and sweet dishes and how certain kinds of restaurants started to cater to these tastes. From the establishment of the first real restaurants in the 1830 until the end of the Civil War, "Ladies' Ordinaries" were set aside as dining rooms where women traveling alone or women in groups could eat in an appropriate environment. After 1850 more accommodation was made for women shopping and later for working women. Places called "ice cream saloons" offered genteel and alcohol-free settings as well as the kinds of food women were thought to prefer. In the latter half of the nineteenth century women had a number of possibilities for lunch, but the evening meal, especially at high-end restaurants, tended to be reserved for women in the company of men. The ability of women to decide where to dine irrespective of the presence of male escorts was related to the creation of casual dining places, and these would take over the restaurant scene after Prohibition.